The Academic Background Of Adapted Physical Education In Brazil (Fiep Bulletin - online, 2021)
Adapted Physical Education (APE) is a remarkable facilitator for rehabilitation, quality of life and social inclusion process of people with disabilities. The academic background of the Physical Education teacher in Brazil is important for the development of sports and physical activities of this population. This essay, through a qualitative approach, aims to conduct a reflection on the academic training of the APE area in Brazil. The academic education of APE in Brazil grows and evolves constantly. There is a noticeable increase in the number of disciplines contemplating the subject in Higher Education Institutions, in both undergraduate and postgraduate courses, emphasizing the knowledge produced by education, research, and extension as a fundamental part of the Physical Education teachers’ curriculum and also improvement actions promoted by government institutions to expand teacher training in Brazil.
Keywords: Adapted Physical Education; Academic background; People with disabilities